La esfera yo-tu en la antropología de Martin Buber: una aplicación a la relación maestro-alumno. - Paredes Moreno, Wandermber Geovanny (2016)
This article is focused on a deepening of the anthropological elements included in the category I-You of Martin Buber, through a bibliographical and analytical research, so as to build the basis of a balanced relationship between student and teacher within the classroom. It is intended to contribute in the debate of the way the educative environment influences the formation path of the student so that he may be autonomous, dynamic, and proactive –based on the confrontation of ideas and the achievement of consent in the solution of conflicts. After writing on the philosophical contextualization of Buber’s thinking, we then proceed to study the pedagogical relationship teacherstudent. The intention here is that of analyzing the reasons for which this thinker focuses his attention on the relational areas that derive from the original relation I-You, so as to be able to construct the necessary methodological strategies for the betterment of the teacher-student relationships, and also to contribute to the decreasing of conflicts in the educative institutions. The conclusion is the proposition of methodological strategies as tools for the solution of the problem upon which this article is focused.